Sebuah Kasus Pankreatitis Kronis pada Seorang Pria dengan Karsinoma Kaput Pankreas - Gerry Setiawan; Gde Somayana (PT Dexa Medica, 2025)
Chronic pancreatitis is a progressive inflammatory disease of the pancreas which leads to loss of exocrine and endocrine function, and is considered difficult to diagnose in the early stage. It is crucial for physicians to have a deep understanding indiagnosed and treated the disease as this could affect the patient’s quality of life and help to prevent further complications.Case report: A 51-year-old male patient, presented to the emergency unit with epigastric pain. Patients also reported yellowing of the eyes and body, followed by dark-colored urine and pale stools. The patient also experienced unintentionalweight loss. Physical examination indicated icteric conjunctiva. Laboratory test result demonstrated the patient had abnormal liver function test and elevated of tumor marker CA 19-9. After underwent magnetic resonance cholangiopancreatography (MRCP), and based on other collected clinical data, it was concluded that the patient had a pancreatic head carcinoma with cholestatic jaundice manifestation. Endoscopic retrograde cholangiopancreatography (ERCP) was performed to release the cholestatic obstruction, subsequently his condition was gradually improved. On follow-up evaluation, the patient underwent endoscopic ultrasonography (EUS) examination, and revealed to have chronic pancreatitis also with multiple stones in the pancreas. This case report will discuss the diagnostic approach and possible treatment for the patient with such condition.